Pengelolaan Minyak dan Gas Bumi (Migas) dalam Ratio Decidendi Putusan Mahkamah Konstitusi Nomor 36/PUU-X/2012 - Arifin, Zainal; Rumawi, Rumawi (International Forum of Researchers and Lecturers, 2024)
The management of oil and gas (Migas) in Indonesian energy law has witnessed a shift towards national control, including provisions in the 1945 Constitution that establish natural resources as state wealth. Law No. 22/2001 regulates various technical, economic, environmental, and community participation aspects of the oil and gas sector. Decisions by the Constitutional Court (MK) have clarified the state's ownership of Migas resources in accordance with the constitution. Renewable energy is crucial for Indonesia's sustainable development, with collaboration between the government and the private sector aimed at increasing the penetration of renewable energy, overcoming financial barriers, and protecting the environment. The MK's decision regarding Law No. 22/2001 supports state sovereignty, the interests of the people, and the goals of preserving natural resources and sustainable development. The key issue at hand is the nature of oil and gas management in Indonesian energy law and whether the legal considerations in the Constitutional Court's decision No. 36/PUU-X/2012 align with Indonesian energy law. The research method employed in this study is a normative juridical approach, also referred to as doctrinal research, which involves the examination of legal documents and literature. Through this research, Indonesia aims to fulfill its commitment to reducing environmental impact and dependence on fossil fuels through renewable energy sources.